Implementasi Sistem Informasi Penjualan dan Pemesanan Bumbu Masak Berbasis Website Toko Melani Menggunakan Waterfall - Muhammad Zulfa Rusdiansyah; Reyginta Ginting; Rizki Sultan Afian (CV. Shofanah Media Berkah, 2026)
Melani Spice Store is a business engaged in selling various cooking spice products. The sales and transaction recording processes are still carried out manually, resulting in inefficient data management, a higher risk of recording errors, and difficulties in generating sales reports. This study aims to design and implement a web-based Sales and Ordering Information System for cooking spice products using the Waterfall development method. Data collection techniques included observation, interviews, and literature study, while the Waterfall method was implemented through the stages of requirement, design, implementation, verification, and maintenance. The system was developed using PHP, HTML, CSS, JavaScript, and MySQL as the database management system. System testing was conducted using the Black Box Testing method to ensure that all system functions operated according to the specified requirements. The results indicate that the developed system is capable of facilitating the computerized management of product data, customer orders, customer information, and sales reports. Furthermore, the system improves the effectiveness and efficiency of business processes, minimizes recording errors, and assists the store owner in monitoring sales activities and managing data more quickly, accurately, and systematically.